Cone-Beam computed tomography assessment of canal-centering ability for traditionally used nickel titanium and nickel titanium files with reciprocating hand piece and wave-one files - Rubeena Tabasum Shaik; Satyanarayana V V Uppalapati; Lavanya Neelima Uppu; Sriramarao Sudhamsetty; D Praneeth Kumar; Maheswari Kumpatla (Wolters Kluwer Medknow Publications, 2021)
Aim of the Study: Need for our study was to evaluate a comparison between canal preparation ability of nickel-titanium (NiTi) hand files with step-back manual technique, of NiTi files installed on a reciprocating hand piece and of Wave-One files utilizing noninvasive cone-beam computed tomography (CBCT) technique. Materials and Methods: Thirty extracted intact single-rooted human mandibular premolars were used in the study, segregated in three sets of 10 specimens each, where canal instrumentation was done by different methods using NiTi in step-back technique, using reciprocating hand piece with NiTi files and using primary file with the use of Wave-One reciprocating system. Later, evaluation of centering ability was conducted using the references through CBCT images. Results: Hand NiTi files showed even less canal centering ability as compared to other two sets. Mesiodistal diameter at 9 mm length of the prepared canal was 1.06 and later was 0.98, which shows excessive preparation in case of Set I versus Set II. In case of comparison between Set III and Set I, mesiodistal diameter at 9 mm length of the prepared canal was 0.99, and later was 1.06, depicting better canal shaping ability with Wave-One file. Conclusion: The use of hand NiTi files installed on a reciprocating hand piece would be economically beneficial producing the similar results as that of wave one without any deviation from the original canal anatomy.